Family Support on Severe Frequency in Epilepsy Patients in RSUP. Dr. Kariadi Semarang - Theresia Ika; Eni Hidayati (Universitas Muhammadiyah Semarang, 2019)
Background: This epilepsy is considered a burden for the patient, the family and is considered an embarrassing disease, infectious disease and mental illness that makes the epileptic patient difficult to live a normal life, often experiencing discrimination in terms of learning, work, or in marriage. Objective: to know family support for the occurrence of seizure frequency in epilepsy patients. Research Method: Type of qualitative research using the phenomenological approach. The sampling technique is done by using purposive sampling approach. Excavation of this data is done by conducting in-depth interviews with the object or the respondent. Results: The support provided by the family in the form of explaining and teaching the treatment of epilepsy, helping and protecting the respondents in the treatment of epilepsy, support in terms of providing treatment and financing and providing love and trust. It is expected that families can provide good support, so that will reduce the incidence of seizure frequency that appears and can improve the quality of life of respondents.